Parameters of acute vasoreactivity testing after balloon pulmonary angioplasty in patients with chronic thromboembolic pulmonary hypertension - Sergey Y. Yarovoy (IP Morozov P.V., 2020)
Aim.To study the effect of balloon pulmonary angioplasty (BPA) on the changes of pulmonary artery pressure, cardiac output and structural parameters of pulmonary arteries after acute vasoreactivity testing (AVT) in inoperable patients with chronic thromboembolic pulmonary hypertension (CTEPH).